The Effect of Implementation OD Scpecial Economic Zones on Regional Physical Facilities and Infrastructure in Muara Satu District Lhokseumawe City - Sutrisno Sutrisno; Tarmizi Tarmizi; Dwi Lindarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to analyze: 1. the influence of environmental conditions on the improvement of physical facilities and infrastructure in the Muara Satu sub-district 2. the influence of inter-organizational relationships on the improvement of physical facilities and infrastructure in the Muara Satu sub-district 3. the influence of resources on the improvement of physical facilities and infrastructure the Muara Satu sub-district 4. the influence of the implementor's institutional character on the improvement of physical facilities and infrastructure in the Muara Satu sub-district. The method used is correlational quantitative, using the exposed facto method. The results of this study are (1) the environmental condition variable has a significant influence on the physical facilities and infrastructure of the area in Muara Satu District, Lhokseumawe City. (2) The inter-organizational relationship variable has a significant influence on the physical facilities and infrastructure of the area in Muara Satu District, Lhokseumawe City. (3) The resource variable has a significant influence on the physical facilities and infrastructure of the area in Muara Satu District, Lhokseumawe City. (4) The variable character of the implementor institution has a significant influence on the physical facilities and infrastructure of the area in Muara Satu District, Lhokseumawe City.